Vaccination coverage of recommended vaccines and determinants of vaccination in at-risk groups - Lise Boey; Eline Bosmans; Liane Braz Ferreira; Nathalie Heyvaert; Melissa Nelen; Lisa Smans; Hanne Tuerlinckx; Mathieu Roelants; Kathleen Claes; Inge Derdelinckx; Wim Janssens; Chantal Mathieu; et al. (Taylor & Francis Group, 2020)
Upon exposure to vaccine-preventable diseases, certain individuals are at increased risk for complications due to preexisting diseases, age or immunosuppressive treatment. Vaccination against influenza, pneumococcal disease and hepatitis B (for some groups) is advised in addition to standard vaccination against diphtheria, tetanus and pertussis. We estimated the vaccination coverage and determinants of recommended vaccinations in patients with diabetes mellitus type 1 (n = 173) and type 2 (n = 177), chronic kidney disease (CKD) (n = 138), heart failure (n = 200), chronic obstructive pulmonary disease (COPD) (n = 187), HIV (n = 201) or solid organ transplantation (SOT) (n = 201) in a monocentric study. Vaccination data were retrieved from documents provided by patients and general practitioners, and from the Flemish vaccination register. Less than 10% had received all recommended vaccines. Overall, 29% of subjects were vaccinated against diphtheria-tetanus, 10% against pertussis, 44% against influenza, 32% against pneumococcal disease and 24% of HIV patients and 31% of CKD patients against hepatitis B. Age was positively associated with vaccination against influenza (OR:2.0, p < .01) and pneumococcal disease (OR:2.6, p < .001). Patients with COPD, HIV and SOT were more likely to be vaccinated against influenza (OR:2.8, p < .001, OR:1.8, p < .05; OR:2.0, p < .001, respectively) and pneumococcal disease (OR:2.9, p < .001, OR:25.0, p < .001; OR:2.6, p < .001, respectively) than patients with heart failure. Reason for non-vaccination were concerns about effectiveness, necessity and side effects of influenza vaccines, and not being aware of the recommendation for pneumococcal disease. Initiatives to monitor the vaccination status of vulnerable patients are needed, which is why we advocate systematic vaccination registration and frequent communication about vaccination.